2023
DOI: 10.1002/smll.202306038
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Heterointegration of 3D Semiconductors on Graphene by Anchor Point Nucleation

Thierno Mamoudou Diallo,
Tadeáš Hanuš,
Gilles Patriarche
et al.

Abstract: The heterointegration of graphene with semiconductor materials and the development of graphene‐based hybrid functional devices are heavily bound to the control of surface energy. Although remote epitaxy offers one of the most appealing techniques for implementing 3D/2D heterostructures, it is only suitable for polar materials and is hugely dependent on the graphene interface quality. Here, the growth of defect‐free single‐crystalline germanium (Ge) layers on a graphene‐coated Ge substrate is demonstrated by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…2D-assisted epitaxy, in theory, could eventually offer infinite reuse of the substrate. However, it is still in relatively early research stages, especially in case of group IV materials such as Ge, which were demonstrated for the first time in late 2022 [39], using a new approach on local nucleation and lateral overgrowth on the 2D interface [40,59]. Moreover, other challenges such as large surface growth and the transfer of high-quality interfaces need to be resolved for its viable application [60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D-assisted epitaxy, in theory, could eventually offer infinite reuse of the substrate. However, it is still in relatively early research stages, especially in case of group IV materials such as Ge, which were demonstrated for the first time in late 2022 [39], using a new approach on local nucleation and lateral overgrowth on the 2D interface [40,59]. Moreover, other challenges such as large surface growth and the transfer of high-quality interfaces need to be resolved for its viable application [60].…”
Section: Resultsmentioning
confidence: 99%
“…The main domains and applications of Ge FSM are illustrated in Figure 1. Various techniques have been demonstrated for Ge FSM fabrication, including substrate thinning [34], epitaxial liftoff [35,36], Smart cut technology [37], mechanical spalling [38], 2Dassisted epitaxy [39,40], and Germanium-on-Nothing [41,42]. Among them, the porosification lift-off technique has recently received significant attention and development thanks to its potentially high-throughput and cost-effective process [20,25].…”
Section: Introductionmentioning
confidence: 99%